2021
DOI: 10.1016/j.crphar.2020.100009
|View full text |Cite|
|
Sign up to set email alerts
|

Drug interaction and chronic obstructive respiratory disorders

Abstract: Chronic obstructive respiratory disorders uncontrolled by monotherapy should be given combinations of drugs that act by distinct mechanisms of action. The rationale for combining different classes of drugs should be to elicit a synergistic interaction, lower the dose of the single components in the combinations and, thus, reduce the risk of adverse events. The aim of this systematic review was to investigate the combined effect of drugs acting on human airways, by including studies that used a valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…An unknown factor in the sensitising serum related to IgE, but not IgE itself, has also been shown to contribute to non-specific AHR observed in isolated airways (Schmidt & Rabe, 2000). Although the precise underlying mechanisms leading to the AHR induced by passive sensitisation are not yet fully understood (Mitchell et al, 1997;Rabe, 1998;Schmidt et al, 1999), it has been extensively demonstrated that this phenomenon is associated with reduced synthesis of cyclic adenosine monophosphate (cAMP) in ASM and increased release of endogenous non-neuronal ACh (Calzetta et al, 2020;Rogliani et al, 2016Rogliani et al, , 2020Rogliani, Ritondo, Zerillo, et al, 2021c).…”
Section: Passive Sensitisation Of Human Airwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…An unknown factor in the sensitising serum related to IgE, but not IgE itself, has also been shown to contribute to non-specific AHR observed in isolated airways (Schmidt & Rabe, 2000). Although the precise underlying mechanisms leading to the AHR induced by passive sensitisation are not yet fully understood (Mitchell et al, 1997;Rabe, 1998;Schmidt et al, 1999), it has been extensively demonstrated that this phenomenon is associated with reduced synthesis of cyclic adenosine monophosphate (cAMP) in ASM and increased release of endogenous non-neuronal ACh (Calzetta et al, 2020;Rogliani et al, 2016Rogliani et al, , 2020Rogliani, Ritondo, Zerillo, et al, 2021c).…”
Section: Passive Sensitisation Of Human Airwaysmentioning
confidence: 99%
“…T A B L E 1 Summary of in vitro and ex vivo models from human airways. Pharmacological pathways can be also evaluated (Calzetta et al, 2011, Calzetta, Pistocchini, et al, 2023b, Manson et al, 2020, Naline et al, 1989, Naline et al, 2018, Rogliani et al, 2015 Isolated (Calzetta et al, 2020;Calzetta, Matera, Facciolo, et al, 2018b;Matera et al, 2011;Mitchell et al, 1997;Rabe, 1998;Rogliani et al, 2016Rogliani et al, , 2020Rogliani, Ritondo, Zerillo, et al, 2021c;Schmidt et al, 1999;Schmidt & Rabe, 2000) Normal (Calzetta, Pistocchini, et al, 2023b;Johnson et al, 1990Johnson et al, , 1992Kroegel et al, 1994;Rabe et al, 1994;Schmidt et al, 2002) Normal In vitro model of asthma / Inflammatory profile, alarmins (TSLP, IL-33 and IL-25) release, and pharmacological pathways can be evaluated (Calzetta, Matera, Facciolo, et al, 2018b;Calzetta, Rogliani, et al, 2014b;Fulcher et al, 2005…”
Section: Exposure To Pollutantsmentioning
confidence: 99%
“…Solid evidence shows that among the various combinations, the ICS/LABA/LAMA triple combination is the one that induces the strongest synergistic bronchorelaxant effect in both the middle bronchi and small airways. 19 However, a translational study suggested that the synergistic interaction observed in vitro when adding a LAMA to the ICS/LABA combination may lead to maximal small airway, but not medium-calibre airway, relaxation in vivo. 20 When salbutamol was administered on top of triple therapy (2 h after the last inhalation of the triple combination) in severe COPD patients after two weeks of treatment, no significant improvement in peripheral resistance, expressed by the difference between resistance at 5 Hz (R5) and resistance at 19 Hz (R19) was detected whereas forced expiratory volume in 1 s (FEV 1 ) increased significantly.…”
Section: Pharmacological and Clinical Evidence Supporting Triple Therapymentioning
confidence: 99%
“…31 Ensifentrine acts as a dual inhibitor of PDE3/4, downstream effector proteins of the sympathetic signalling pathway triggered by β2-adrenoceptors. 32 As a result, it raises cAMP levels. Ensifentrine and LAMAs, in contrast, work on different signal transduction pathways that ultimately combine to produce the ASM bronchorelaxant effect.…”
Section: Perspectivesmentioning
confidence: 99%